Correction: miRNAs in the vitreous humor of patients affected by idiopathic epiretinal membrane and macular hole - Russo, Andrea; Ragusa, Marco; Barbagallo, Cristina; Longo, Antonio; Avitabile, Teresio; Uva, Maurizio G.; Bonfiglio, Vincenza; Toro, Mario D.; Caltabiano, Rosario; Mariotti, Cesare; Boscia, Francesco; Romano, Mario R.; et al. (PloS one, 2017)
[This corrects the article DOI: 10.1371/journal.pone.0174297.].